2019
DOI: 10.1111/nmo.13532
|View full text |Cite
|
Sign up to set email alerts
|

Functional anal canal length measurement using high‐resolution anorectal manometry to investigate anal sphincter dysfunction in patients with fecal incontinence or constipation

Abstract: Background Using high‐resolution anorectal manometry, we aimed to evaluate the: (a) optimal threshold to measure functional anal canal length (FACL) with intra‐ and inter‐observer variability; (b) relationship between abnormal FACL and other phenotypic findings; and (c) utility of FACL measurement to discriminate between healthy volunteers (HV) and patients with fecal incontinence (FI) or chronic constipation (CC). Methods Consecutive patients referred for investigation of FI or CC in isolation were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 54 publications
0
32
0
1
Order By: Relevance
“…Sensors 5 and 6 may be located either in the rectum or in the anal canal. In a prior study, sensors that recorded pressures, which were 20 mmHg greater than rectal pressure, were considered to be in the anal canal 25 . At rest, the rectal pressure is approximately 10 mmHg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors 5 and 6 may be located either in the rectum or in the anal canal. In a prior study, sensors that recorded pressures, which were 20 mmHg greater than rectal pressure, were considered to be in the anal canal 25 . At rest, the rectal pressure is approximately 10 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…In a prior study, sensors that recorded pressures, which were 20 mmHg greater than rectal pressure, were considered to be in the anal canal. 25 At rest, the rectal pressure is approximately 10 mmHg. Hence, in this study, sensors that recorded a resting pressure of 30 mmHg or greater were considered to be in the functional anal canal.…”
Section: New Analysismentioning
confidence: 99%
“…Nevertheless, recent 3D HD-ARM studies have shown that sustained voluntary contraction (long squeeze) is the most discriminant parameter to differentiate constipated and incontinent patients [32]. Similarly, other measures, consistently reported using conventional manometry studies, have not been considered essential by the IAPWG [10••], including functional anal canal length [33], anal relaxation during push and sustained urgency volume during the rectal sensory test. Further, the recto-anal pressure gradient (RAPG) during push has not been incorporated.…”
Section: The London Classification For Disorders Of Anorectal Functionmentioning
confidence: 99%
“…We did nd a signi cant difference in the functional anal canal length between participants with BMI < 25 and those with BMI ≥ 25, suggesting that BMI variation could affect the functional anal canal length. In the study conducted by Paul et al, functional anal canal length was used to evaluate anal sphincter dysfunction in patients with fecal incontinence or constipation, using baseline values collected from a healthy volunteer control group [18]. However, functional anal canal length did not help diagnosis of fecal incontinence or constipation in that study.…”
Section: Discussionmentioning
confidence: 94%